Improved Optimal Sizing of Hybrid PV/Wind/Battery Energy Systems - Gursoy, Gunes; Baysal, Mustafa (IEEE, 2014)
Renewable energy resources have come into prominence as a solution to increased energy demand worldwide. Since the nature of the some renewable energy resources (RES) such as solar and wind energy is intermittent, the reliability of the system supplied from those sources is low. A hybrid energy system combining the several RES is one of the viable solutions to increase the reliability of the system. This paper develops a optimal sizing method for hybrid energy systems incorporating photovoltaic (PV), wind and battery components. In the developed model, the effects of variations in air density and PV conversion efficiency on the generated energy amount are considered in the calculation resulting in more accurate optimal sizing. A remote area in Texas State, USA, is chosen for optimal sizing of hybrid PV/wind/battery energy system based on the case study. Meteorological data such as solar radiation, wind speed and ambient temperature is modified and then converted to useful energy. In order to avoid using excessive battery capacity, the demand response technique is applied for the situation in which energy demand is much more than energy generation. The results show that assuming air density and PV conversion efficiency to be constant causes about 15% and %20 deviation in calculation, respectively. The demand response method also provide saving of 28% in capital cost.
Keywords: hybrid energy systems; demand response; optimization; solar PV; wind; Energy & Fuels